7B.01: FINAL ANALYSIS ON ADHERENCE TO ANTIHYPERTENSIVE MEDICATION IN TREATMENT RESISTANT HYPERTENSION (TRH) UNDERGOING RENAL DENERVATION (RDN). (June 2015) - Schmieder, R.E.; Ott, C.; Veelken, R.; Schmid, A.; Uder, M.; Toennes, S.W.
Abstract : Objective: Adherence to medication has been repeatedly proposed to represent a major cause of TRH and may affect the BP response to antihypertensive interventions. We assessed adherence rates in patients with TRH at baseline at 6 months after RDN and the potential impact BP response. Design and method: 80 patients with TRH have been included in two prospective observational follow-up studies (clinicaltrials.gov, NCT01442883 and NCT01687725) that focus on potential antihypertensive and nephroprotective effects of renal denervation (RDN). After ethical approval on 23.08.2013 we retrospectively approached each patient to give us informed consent for analyzing urine samples that had been collected at baseline and 6 months after renal denervation for toxicological urine analysis (by liquid chromatography-mass spectrometry analysis (LC-MS)) of antihypertensive compounds or metabolites. In addition to office BP, 24-h ambulatory BP (ABP) (Spacelab) and central hemodynamics (Sphygmocor) were assed as well. Results: Informed consent was obtained in 79 patients (mean age 60.4 ± 10 years (ABP: 155 ± 14/88 ± 13 mmHg). All meds were detected at baseline in N = 44 or 56 % [6 month after RDN: in N = 52 or 66%] 1 med was missing in N = 22 or 28% [N = 17 or 22%],  >  = 2 meds in N = 13 or 16% [N = 10 or 13%] of whom N = 3 did not take any meds at all (p = 0.049) and central systolic pressure (p = 0.012) was higher in non-adherent patients (p = 0.049). A shift analysis revealed that adherence remained the same in 47 subjects (in 35 Ss all meds, in 6 Ss 1 med missing and in 6 Ss > = 2 meds missing), whereas in 21 Ss adherence increased and in 11 Ss decreased after RDN. Adherence did not significantly change (Mc Nemar-Bowker Test, p = 0.362). The decrease in 24-h ABP was not different in those taking all medication at 6 months visit (-7 ± 13 mmHg) compared to those with an increased (-10 ± 13 mmHg) and decreased adherence (-7 ± 14 mmHg) (all p > 0.20). Conclusions: In our tertiary referral center in Northern Bavaria, Germany, non-adherence to medication in patients with TRH was relatively low. Adherence pattern did not change significantly and had no impact on the overall reported BP changes after RDN.